The Routledge Companion to Education. - Arthur, James (Taylor & amp; Francis, 2011)
Who are the key thinkers in education? What are the hot topics in education? Where will education go from here? The Routledge Companion to Education presents the most comprehensive, up-to-date guide available to the key theories, themes and topics in education. Forty specially commissioned chapters, covering all aspects of education, introduce you to the ideas, research and issues that have shaped this most diverse, dynamic and fluid field. Part one provides an introduction to the key theories, thinkers and disciplines within education Part two covers ideas and issues about how, what and why l.